The Activity and Specificity of the Outer Membrane Protein Chaperone SurA Are Modulated by a Proline Isomerase Domain - Dante P. Ricci (American Society for Microbiology, 2013)
ABSTRACT SurA is a component of the periplasmic chaperone network that plays a central role in biogenesis of integral outer membrane β-barrel proteins (OMPs) in Escherichia coli. Although SurA contains two well-conserved proline isomerase (PPIase) domains, the contribution of these domains to SurA function is unclear. In the present work, we show that defects in OMP assembly caused by mutation of the β-barrel assembly factors BamA or BamB can be corrected by gain-of-function mutations in SurA that map to the first PPIase domain. These mutations apparently bypass the requirement for a stable interaction between SurA and the Bam complex and enhance SurA chaperone activity in vivo despite destabilization of the protein in vitro. Our findings suggest an autoinhibitory mechanism for regulation of SurA chaperone activity through interdomain interactions involving a PPIase domain. We propose a model in which SurA activity is modulated by an interaction between SurA and the Bam complex that alters the substrate specificity of the chaperone. IMPORTANCE The dominant surA mutations described here alter amino acid residues that are highly conserved in eukaryotic homologs of SurA, including Pin1, the human proline isomerase (PPIase) implicated in Alzheimer’s disease and certain cancers. Consequently, a mechanistic description of SurA function may enhance our understanding of clinically important PPIases and their role(s) in disease. In addition, the virulence of Gram-negative bacterial pathogens, such as Salmonella, Shigella, and Escherichia coli O157:H7, is largely dependent on SurA, making this PPIase/chaperone an attractive antibiotic target. Investigating the function of SurA in outer membrane (OM) biogenesis will be useful in the development of novel therapeutic strategies for the disruption of the OM or the processes that are essential for its assembly.